Awareness on labour pain relief among post-partum women in Kwara State, North-Central Nigeria - Bilikisu, Abubakar Ayinla (2020)
Delivery is very painful and most severe experience women undergo in life. Intrapartum analgesia can be employed to relieve the pain of child labour. Despite this, the use of intrapartum analgesia is controversial, as some advocate for normal delivery without analgesia which deprived women the fundamental right of pain relief in labour. The objective of this study is to assess women’s awareness on labour pain relief in Kwara State, North-Central, Nigeria. A cross-sectional study was conducted among 685 post-partum women at Kwara State Hospitals. A structured questionnaire was used to collect information from women within six weeks of post-delivery. The data collected were analyzed using the Statistical Package for Social Sciences (SPSS) software version 23. Chi-square test and Logistic regression were used to confirm the association between the sociodemographic characteristics of the respondents’ awareness. The study revealed that less than half of the respondents (46.4%) were aware of labour pain relief whereas 486 are willing to accept pain relief in their subsequent delivery. Chi-square test revealed that occupation and level of education was significantly associated with awareness of labour pain relief with p-value 0.001 and 0.000 respectively. Result of logistic regression shows that level of education significantly predicts awareness. The outcome of this study reveals that post-partum women need to be enlightened on labour pain relief. The women can be educated by dissemination of information at the antenatal classes and by the distribution of pamphlets on labour pain relieaf. Thus, the facilities required for the administration and monitoring of intrapartum analgesia should also be provided at the delivery suits.